Intragastric balloon insertion and pancreatitis: Case series. (2020) - Alqabandi, Omar; Almutawa, Yousef; AlTarrah, Dana; Alhajeri, Mufarrej; Jamal, Mohammad H.; Almazeedi, Sulaiman
Highlights: Intra-Gastric Balloon use as non-operative strategy for bariatric patients. Rise of adverse life-threatening outcomes of Intra-Gastric Balloon. Pancreatitis could be secondary to pancreas compression by the Intra-Gastric Balloon. Need for the recognition of balloon pancreatitis as a complication of Intra-Gastric Balloon insertion. Abstract: Introduction: Obesity is a complex multifactorial disease that affects populations worldwide. In Kuwait, the prevalence of obesity is a major public health problem. Intra-Gastric Balloon (IGB) is commonly used as a non-operative strategy among bariatric patients. However, with the increasing use of IGB, life-threatening adverse outcomes are widely reported. Presentation of cases: A case series five patients presenting with pancreatitis from IGB in Kuwait is reported to better investigate the emerging complications of IGB. Three types of IGB were inserted, these include the Orbera Intragastric Balloon System, Orbera365 Intragastric Balloon System, and the Spatz Adjustable Gastric. The clinical course of balloon pancreatitis is described. Discussion: The case series examined existing case reports of IGB associated pancreatitis in the literature, in addition to the investigated clinical outcomes. Patients presented with mild pancreatitis, and removal of balloon resulted in significant improvement in symptoms. Pathogenesis of balloon pancreatitis could be secondary to the pancreas compression by the IGB. Conclusion: Despite the rarity of balloon pancreatitis, it needs to be recognized as a complication of IGB insertion. Further research is needed to better understand the implications of the balloon size, shape, volume and location of balloon insertion in order to prevent this fatal complication.